2021
DOI: 10.1007/s00382-020-05573-z
|View full text |Cite
|
Sign up to set email alerts
|

Air-Sea interaction over the Gulf Stream in an ensemble of HighResMIP present climate simulations

Abstract: A dominant paradigm for mid-latitude air-sea interaction identifies the synoptic-scale atmospheric “noise” as the main driver for the observed ocean surface variability. While this conceptual model successfully holds over most of the mid-latitude ocean surface, its soundness over frontal zones (including western boundary currents; WBC) characterized by intense mesoscale activity, has been questioned in a number of studies suggesting a driving role for the small scale ocean dynamics (mesoscale oceanic eddies) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
48
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(55 citation statements)
references
References 53 publications
5
48
2
Order By: Relevance
“…Such new models have shown improvements in the representation of various aspects of weather and climate variability, including blocking frequency over the Pacific and Atlantic (Schiemann et al, 2020), the distribution of precipitation over Europe (Demory et al, 2020), tropical cyclones (M. J. Vannière et al, 2020;Vidale et al, 2021;Zhang et al, 2021), air-sea interactions over the Gulf Stream (Bellucci et al, 2021), and Atlantic Ocean heat transports (M. J. Roberts et al, 2020b).…”
Section: Introductionmentioning
confidence: 99%
“…Such new models have shown improvements in the representation of various aspects of weather and climate variability, including blocking frequency over the Pacific and Atlantic (Schiemann et al, 2020), the distribution of precipitation over Europe (Demory et al, 2020), tropical cyclones (M. J. Vannière et al, 2020;Vidale et al, 2021;Zhang et al, 2021), air-sea interactions over the Gulf Stream (Bellucci et al, 2021), and Atlantic Ocean heat transports (M. J. Roberts et al, 2020b).…”
Section: Introductionmentioning
confidence: 99%
“…The basic of the coupling between the different components is described in Fogli and Iovino (2014). The single components of the coupled model are described in detail in Cherchi et al (2019); additional studies based on CMCC GCM can be found in Scoccimarro et al 2017a, Bellucci et al 2021. No changes are applied in terms of parameterization choices -and relative tuning parameters -moving from HR to VHR.…”
Section: The Numerical Experimentsmentioning
confidence: 99%
“…More recently, the community-wide effort made in the framework of the HighresMIP project (Haarsma et al, 2016) further demonstrated the capability of high resolution models of improving several characteristics of the mean climate and its variability (e.g. Roberts et al, 2020;Fabiano et al, 2020;Bellucci et al, 2021;Zhang et al, 2021). More generally, recent outcomes from the Coupled Model Intercomparison Project Phase 6 (CMIP6, Eyring et al, 2016) also highlighted that -on averagehigher resolution GCMs outperform lower resolution ones (e.g.…”
Section: Introductionmentioning
confidence: 99%